2019
DOI: 10.1080/22423982.2019.1653139
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about heart failure and self-care persists following outpatient programme- a prospective cohort study from the Faroe Islands

Abstract: Objectives: Longer life expectancies imply increased prevalence of heart failure. Blittle is known about the maintenance of disease specific knowledge following patient education. Our aim was to investigate if self-care and heart failure knowledge persists at 9 month follow up among patients with heart failure after an outpatient programme in the Faroe Islands. Methods: A prospective cohort study with patients recently diagnosed with heart failure were recruited and evaluated by questionnaire at baseline, afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
1
9
0
3
Order By: Relevance
“…This may be due to the fact that most people in this study received low educational levels (only read and write or secondary education), they usually don't care to know more about their diseases, or it may be because they didn't find the chance to be educated and aware of their diseases from trustworthy and professional persons like the health care team. This finding is in agreement with Róin et al (2019), who stated that the mean knowledge score at baseline was 9.9 (2.5), which improved to 12.6 (1.5) at 3 months with a p value of <0.001 in their study that assessed the knowledge of patients about heart failure. They attribute the low level of knowledge to the respondents' educational level and whether they had received high-quality education.…”
Section: Discussionsupporting
confidence: 91%
“…This may be due to the fact that most people in this study received low educational levels (only read and write or secondary education), they usually don't care to know more about their diseases, or it may be because they didn't find the chance to be educated and aware of their diseases from trustworthy and professional persons like the health care team. This finding is in agreement with Róin et al (2019), who stated that the mean knowledge score at baseline was 9.9 (2.5), which improved to 12.6 (1.5) at 3 months with a p value of <0.001 in their study that assessed the knowledge of patients about heart failure. They attribute the low level of knowledge to the respondents' educational level and whether they had received high-quality education.…”
Section: Discussionsupporting
confidence: 91%
“…Our study sought to evaluate the effects of a programme covering a range of topics focussed on 'learning about' in order to 'live with' Heart Failure and sought to address many of these misconceptions in group discussions. While we did not set out to measure the degree of knowledge acquisition, evidence suggests that disease-specific outpatient-based multidisciplinary programmes like ours can produce durable and more accurate knowledge that supports and educates Heart Failure patients (Róin et al 2019).…”
Section: Discussionmentioning
confidence: 98%
“…17 A previous study showed that the higher the knowledge the better their self-care level, even 9 months after being discharged from the hospital. 18,19 This is because knowledge is closely related to education received by patients from a health care professional. This plays a critical role in patient self-care regiment, form an understanding of weight management, daily intake, lowering alcohol level, smoking reduction, daily physical exercise, medication, and adhering to health care professional.…”
Section: Significance For Public Healthmentioning
confidence: 99%